Experimental Investigation of Influence of Crack Parallel Tension on Fracture Energy in Carbon Fiber Composites - Vemparala, Ashok HVS (My University, 2025)
This work investigates the influence of crack-parallel tensile stress on the global Mode I interlaminar fracture behavior of carbon fiber polymeric matrix composites. Traditional Linear Elastic Fracture Mechanics (LEFM) assumes that stresses parallel to a crack have negligible impact on fracture toughness, an assumption challenged by recent studies such as the Gap Test. In quasibrittle materials like fiber-reinforced composites, the presence of crack-parallel stress can significantly modify crack propagation, fracture energy, and the associated fracture process zone (FPZ). The study's goal is to quantify these effects systematically through controlled experiments and to provide insights into fracture mechanics beyond conventional assumptions. By understanding how parallel stresses alter crack growth and energy dissipation, this work helps improve predictive models for composite structures, providing a valuable reference for academic research and practical applications. The findings aim to refine the characterization of composite fracture behavior, highlighting the need for methods that account for FPZ effects under complex stress states. A novel experimental method, the Half-Open I test, was developed to investigate the effect of crack-parallel tension on Mode I fracture. Specimens consist of cross-ply IM7/977-3 carbon fiber laminates with a controlled initial crack introduced using a Teflon film. The key innovation involves inserting a GFRP tab into the crack seam, generating a bending moment at the crack front that induces tension along the crack propagation direction while simultaneously applying a crack-opening moment. By varying tab thickness, the magnitude of the induced bending moment and parallel tension is systematically controlled. Crack propagation is tracked using high-resolution imaging, with crack lengths measured at regular intervals. The negative geometry of the design promotes stable crack growth, providing an advantage over traditional DCB tests. However, the only limitation is the inapplicability of Bazant's size effect law, preventing direct estimation of fracture energy and FPZ size. The experiments reveal that increasing the thickness of the inserted tab, and consequently the crack-parallel tension, enhances the fracture resistance of the composite. Measured crack propagation lengths are converted into energy release rates using Abaqus finite element simulations, and R-curves are reconstructed for each tab thickness and laminate. Despite data noise, trends indicate an rightward shift in fracture energy with increasing parallel stress, suggesting that low-to-moderate crack-parallel tension strengthens the laminate through mechanisms such as fiber bridging and extended FPZ development. Thicker tabs produce more stable crack propagation, while thinner tabs exhibit initial instability. These findings demonstrate that Mode I fracture energy in composites is not a fixed material property but is influenced by the local stress state, challenging traditional LEFM assumptions. Overall, the study provides a robust methodology for assessing crack-parallel effects and highlights the importance of incorporating FPZ considerations in modeling and designing composite structures.
Thesis (Master's)--University of Washington, 2025
Keywords: Carbon Fiber Reinforced Composites; Composites; Finite Element Method; Fracture; Quasi-Brittle; Aerospace engineering; Aeronautics and astronautics